Manajemen Pembiayaan Pendidikan Madrasah Tsanawiyah Satu Atap - Asep Rahman Sudrajat (MANAZHIM, 2019)
To realize optimal education madrasas can not be separated from professional management, it can happen if supported by adequate funding sources, because education without financing will not run. The cost of education is a very important component for the achievement of learning in schools. Giving Bos funds by the government is a breakthrough program to help school funding, but in the process of implementation it has many obstacles as experienced by the One Roof Madrasah Tsanawiyah Syifaurrhman Tasikmalaya such as delays in disbursing BOS funds, of course this can hamper the learning process. This study discusses financing management in the One Roof Madrasah Tsanawiyah Syifaurrahman Tasikmalaya which includes planning, implementing and monitoring funding. This type of research uses descriptive qualitative methods, while data collection techniques use observation, interviews and documentation. Then verify the validity of the data by triangulating data. The results showed that the financing management at MTs SA Syifaurrahman Tasikmalaya went through several stages including financing planning by analyzing the needs of madrasas for one year by a committee formed by the school principal, then the financing was carried out with the proper use of costs according to periodic needs, supervision financing is carried out by the Ministry of Religion, evaluation is carried out by reporting the details of costs incurred during one period by enclosing all transaction evidence.